(untitled) (Biological Sciences - PJSIR, 2005)
Density (r/103 kg m-3) and molal volumes (Vf /10-6 m3 mol-1) of glycine, valine and leucine from 0.03 to 0.07 mol kg-1, and cetyl pyridinium chloride (CPC) and cetyl pyridinium bromide (CPB) were measured in 0.0497 mol kg-1 aqueous surfactant solution systems at different temperatures. The data were regressed against molality, and constants were referred to as the limiting density (r0) and apparent molal volumes (Vf0) and denoted as solute-solvent interactions, while their slope constants indicated molecular interactions and influence of composition. It was observed that amino acids with a shorter alkyl chain, such as glycine, had weaker affinity to interact with cationic surfactants, in comparison with the longer alkyl chain amino acids, such as leucine. The CPB with larger-sized anion showed greater molecular interaction with amino acids.